2016
DOI: 10.1093/ndt/gfw392
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risk of renal replacement therapy in Europe: a population-based study using data from the ERA-EDTA Registry

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 Lifetime risk of renal replacement therapy in Europe: a populationbased study using data from the ERA-EDTA Registry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(30 reference statements)
2
11
0
3
Order By: Relevance
“…Our study showed considerable sex-dependent differences in the lifetime risk of ESKD in Japan. This is in line with previous studies from other countries [12][13][14] that have found that men have higher lifetime risks of ESKD than women. Using cohort data of adults residing in Alberta, Canada, the lifetime risk of ESKD among those without ESKD at age 40 years was estimated to be 2.66% (95% CI 2.57-2.75%) for men and 1.76% (95% CI 1.69-1.83%) for women [12].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed considerable sex-dependent differences in the lifetime risk of ESKD in Japan. This is in line with previous studies from other countries [12][13][14] that have found that men have higher lifetime risks of ESKD than women. Using cohort data of adults residing in Alberta, Canada, the lifetime risk of ESKD among those without ESKD at age 40 years was estimated to be 2.66% (95% CI 2.57-2.75%) for men and 1.76% (95% CI 1.69-1.83%) for women [12].…”
Section: Discussionsupporting
confidence: 93%
“…Using cohort data of adults residing in Alberta, Canada, the lifetime risk of ESKD among those without ESKD at age 40 years was estimated to be 2.66% (95% CI 2.57-2.75%) for men and 1.76% (95% CI 1.69-1.83%) for women [12]. Using European Renal Association-European Dialysis and Transplant Association (ERA-EDTA) Registry data, the cumulative lifetime risk of ESKD up to age 90 years in Europe was estimated to be 1.40% or 0.73% for 40-year-old men or women, 1.32% or 0.68% for 50-year-old men or women, and 1.18% or 0.58% for 60-year-old men or women, respectively [13]. Using data from the United States Renal Data System (USRDS), the cumulative lifetime risk of ESKD from birth to age 100 + years in the total US population was estimated to be 3.96% (95% CI 3.93-3.99%) for men and 2.84% (95% CI 2.69-2.74%) for women [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Per un paziente di 40 anni di sesso maschile negli USA, in Canada e in Europa, tale rischio si aggira intorno al 3,3%, al 2,7% e all'1,4%. In rapporto, nelle donne il rischio è inferiore e, rispettivamente, del 2,2%, dell'1,8% e dello 0,7% (20)(21)(22). La spiegazione potrebbe essere la maggiore progressione della MRC segnalata negli uomini, pur non escludendo l'ipotesi che le donne non abbiano le stesse opportunità di iniziare il trattamento dialitico, che hanno una maggiore propensione a optare per la terapia conservativa, fino all'ipotesi di una maggiore mortalità pre-ESRD.…”
Section: La Prevenzione Inizia Dall'identificazione E Dalla Cura Dei Fattori DI Rischio: Quali Sono Quelli Sesso-specifici Di Sviluppare unclassified
“…Increased survival among the general population has been shown to coincide with lower mortality rates among dialysis patients ( 9 ). Even at constant incidence rates, the size of the RRT population may be expected to increase simply because dialysis patients are living longer ( 8 , 10 ). The latest findings indicate that there is a strong direct correlation between life expectancy and RRT prevalence at the country level ( 5 ).…”
Section: Introductionmentioning
confidence: 99%